3D PRINTER EXTRUDER DESIGN FOR PRINTING WITH DEFORMABLE MATERIALS - Aurelian Zapciu; Catalin Gheorghe Amza; Diana Popescu (Nonconventional Technologies Review, 2017)
This paper presents the replacement of a conventional FDM 3D printer extruder which uses thermoplastic filament with a new extrusion device that can extrude deformable materials. The paper presents the development process, design choices made by the authors and discusses their advantages and disadvantages. The extruder's container which stores the build material is a syringe made out of chemically-resistant plastic material. This container can be loaded with deformable materials such as gel, paste or clay and inserted in the device. A plunger pushes the build material through a nozzle, carrying out the extrusion process. The plunger is actuated using a drive screw-nut mechanism driven by one of the 3D-printer's stepper motors. Other features of the new extrusion device are the capability to heat build material up to 85oC with the use of the 3D-printer's ceramic heaters and to cool the material once it's deposited on the build plate with the use of a side-mounted fan. A prototype device was built with parts manufactured using the 3D printer and thermoplastic extruder which it is meant to replace. The design choices make possible the installation of the device on the desktop 3D printer without any additional electronics.